(untitled) (Journal of Engineering, 2023)
This study examines the vibrations produced by hydropower operations to improve embankment dam safety. This study consists of two parts: In the first part, ANSYS-CFX was used to generate a three-dimensional (3-D) finite volume (FV) model to simulate a vertical Francis turbine unit in the Mosul hydropower plant. The pressure pattern result of the turbine model was transformed into the dam body to show how the turbine unit’s operation affects the dam’s stability. The upstream reservoir conditions, various flow rates, and fully open inlet gates were considered. In the second part of this study, a 3-D FE Mosul dam model was simulated using an ANSYS program. The operational turbine model’s water pressure pattern is conveyed to the dam’s turbine-shared zone. The maximal and minimal upstream reservoir water levels were investigated. A control program was created depending on the principle stress model results collected from the operation of the hydropower plant with the minimum principal stress on the dam body. This research suggests an enhanced turbine operating system, reducing stress on the dam body and increasing dam operation life.